2020
DOI: 10.1039/d0dt01908a
|View full text |Cite
|
Sign up to set email alerts
|

Novel ferrocenyl functionalised phosphinecarboxamides: synthesis, characterisation and coordination

Abstract: Ru(ii) and Rh(iii) complexes of the primary phosphinecarboxamide FcNHC(O)PH2 undergo facile dehydrohalogenation to produce phosphide-bridged dimers as syn and anti isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…67 In 2020, Goicoechea and Štěpnička et al reported the synthesis of ferrocenyl-substituted phosphinecarboxamides, FcNHC(O)PH 2 ( 68 ; Fc = ferrocenyl) and FcCH 2 NHC(O)PH 2 ( 69 ) with terminal PH 2 groups by the reaction of [Na(dioxane) x ](OCP) with aminoferrocene and (ferrocenylmethyl)ammonium chloride, respectively (Schemes 23 and 24). 68 The 31 P NMR of these phosphaureas showed resonance at δ = −129.8 ( 68 ) and −132.8 ( 69 ) ppm, corresponding to PH 2 groups. The crystal structures revealed that the cyclopentadienyl (Cp) moieties were tilted by 3.5(2)° in 68 and 1.8(2)° in 69 , and the amide plane was twisted by 5.4(2)° in 68 and 12.6(2)° in 69 with respect to the Cp ring.…”
Section: Reactivity Of Ocp− Towards Main-group Elementsmentioning
confidence: 95%
“…67 In 2020, Goicoechea and Štěpnička et al reported the synthesis of ferrocenyl-substituted phosphinecarboxamides, FcNHC(O)PH 2 ( 68 ; Fc = ferrocenyl) and FcCH 2 NHC(O)PH 2 ( 69 ) with terminal PH 2 groups by the reaction of [Na(dioxane) x ](OCP) with aminoferrocene and (ferrocenylmethyl)ammonium chloride, respectively (Schemes 23 and 24). 68 The 31 P NMR of these phosphaureas showed resonance at δ = −129.8 ( 68 ) and −132.8 ( 69 ) ppm, corresponding to PH 2 groups. The crystal structures revealed that the cyclopentadienyl (Cp) moieties were tilted by 3.5(2)° in 68 and 1.8(2)° in 69 , and the amide plane was twisted by 5.4(2)° in 68 and 12.6(2)° in 69 with respect to the Cp ring.…”
Section: Reactivity Of Ocp− Towards Main-group Elementsmentioning
confidence: 95%
“…Phosphinecarboxamides R 2 PC(O)NR′ 2 and phosphinecarbothioamides R 2 PC(S)NR′ 2 are phosphorus-analogs of urea and thiourea, and these are interesting compounds in coordination chemistry because of the variety of coordination modes. These compounds are known to act as a P -coordinated monodentate ligand (type I) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], a P,S -coordinated bidentate ligand forming a four-membered chelate ring (type II for phosphinecarbothioamide) [ 8 , 9 , 10 , 11 , 12 , 13 ], and a bridging ligand for two metal centers (type III and type IV for phosphinecarbothioamide) [ 7 , 14 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further research into the synthesis of phosphinecarboxamides has included mechanochemical methods, 16 metal-catalysed reactions, 17 direct reaction of secondary phosphines with cyanates, 18 and phosphinoboration of isocyanates. 19 The reactivity of such species has also been demonstrated by coordination to metal centres, 20 functionalization of P–H bonds to afford secondary phosphines, 11,21 and their use as precursors to generate phosphonates. 22…”
Section: Introductionmentioning
confidence: 99%